Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Disclosure Corporate Social Responisibility (CSRD) Pada Perusahaan Pertambangan Di Bei - Miftahul Jannah; Rian Oktavianie (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2023)
Effect of profitability, firm size, board of commissioners, and public share ownership of CSR Disclosure.The purpose of this study is to determine the effect of profitability, firm size, board of commissioners, and public share ownership of CSR Disclosure. The type of research used is associative. The data used is secondary data. Data collection techniques used in this study is document analysis. Data analysis method used in this research is qualitative and quantitative analysis.The results show that there is influence between board of commissioner of CSR disclosure and not influence between profitability, firm size and public share ownership of CSR disclosure.